Respuesta :
Answer:
f(- 6) = 9
Step-by-step explanation:
to evaluate f(- 6), substitute x = - 6 into f(x)
f(- 6) = - [tex]\frac{2}{3}[/tex] × - 6 + 5
= - [tex]\frac{2(-6)}{3}[/tex] + 5 = 4 + 5 = 9
f(- 6) = 9
How do you identify a function?
- Find the highest power of x to determine the degree of the function.
- Identify the term containing the highest power of x to find the leading term.
- Identify the coefficient of the leading term.
What does the word function mean in math?
- f (3) f ( 3) and g(3) g ( 3)
- f (−10) f ( − 10) and g(−10) g ( − 10)
- f (0) f ( 0)
- f (t) f ( t)
- f (t +1) f ( t + 1) and f (x +1) f ( x + 1)
- f (x3) f ( x 3)
- g(x2−5) g ( x 2 − 5)
to evaluate f(- 6), substitute x = - 6 into f(x)
f(- 6) = - [tex]\frac{2}{3}[/tex] × - 6 + 5
= - [tex]\frac{2(-6)}{3}[/tex] + 5 = 4 + 5 = 9
hence f(- 6) = 9
Learn more about function here Learn more about function here brainly.com/question/12431044
#SPJ2